2015
DOI: 10.1177/1203475415586664
|View full text |Cite|
|
Sign up to set email alerts
|

Non-melanoma Skin Cancer in Canada Chapter 4: Management of Basal Cell Carcinoma

Abstract: Background: Basal cell carcinoma (BCC) is the most common malignancy. Growth of BCCs leads to local destruction of neighbouring healthy skin and underlying tissue and can result in significant functional and cosmetic morbidity. Objective: To provide guidance to Canadian health care practitioners regarding management of BCCs. Methods: Literature searches and development of graded recommendations were carried out as discussed in the accompanying Introduction. Results: Although BCCs rarely metastasize, they can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 93 publications
(125 reference statements)
0
39
1
2
Order By: Relevance
“…Permanent hypo‐pigmentations after imiquimod treatment have been reported as an adverse event . Our network meta‐analysis could not distinguish the doses or frequency of imiquimod regimen, but some reports showed that the frequent use of high doses could work better with potentially more severe adverse events such as pruritus and pain . Although a RCT described the similar efficacy and cosmetic outcomes of FU to those of imiquimod, imiquimod showed the lower recurrence rate than FU in our study .…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Permanent hypo‐pigmentations after imiquimod treatment have been reported as an adverse event . Our network meta‐analysis could not distinguish the doses or frequency of imiquimod regimen, but some reports showed that the frequent use of high doses could work better with potentially more severe adverse events such as pruritus and pain . Although a RCT described the similar efficacy and cosmetic outcomes of FU to those of imiquimod, imiquimod showed the lower recurrence rate than FU in our study .…”
Section: Discussioncontrasting
confidence: 61%
“…Although a RCT described the similar efficacy and cosmetic outcomes of FU to those of imiquimod, imiquimod showed the lower recurrence rate than FU in our study . Cryotherapy uses liquid nitrogen to destroy tumour through freezing and is reported to be effective especially for some BCC . However, our network meta‐analysis focusing on treatment failure showed approximately 20 times higher odds compared with surgery.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…These searches were independent from the searches used to research the treatment chapters in these guidelines (Chapters 3, 4, and 5). [101][102][103] Reference lists from recent review articles were examined to identify additional studies. Clinical trials with the highest level of evidence were included.…”
Section: Methodsmentioning
confidence: 99%